Escitalopram Induced Serotonin Syndrome: A Case Report - Mistry, Mahek; Chandrakar, Vikas R.; Rajput, Hemraj Singh (Indian Journal of Pharmacy Practice)
Escitalopram is a selective serotonin reuptake inhibitor (SSRI) and S-enantiomer of racemic escitalopram, enhances serotonergic activity in the central nervous system (CNS). It is indicated for the Major depressive disorder and Generalized Anxiety Disorder. It is having SEROTONIN SYNDROME as a major side effect. Other uses are OCD, panic disorder, premenstrual dysphoric disorder, social phobia, depression due to severe trauma and mix anxiety and depressive disorder. A 13 year old female child had complain of headache and the hiccups for that she went to hospital from their she was prescribed with the Tab. CLONAZEPAM (2.5 mg, ½ Tab, hs) and Tab. ESCITALOPRAM (5 mg, ½ Tab, hs) for 4 days and followed by 1 Tab. hs. Patient had completed duration of half tablet of ESCITALOPRAM and took full tablet and after 1-2 hour she developed up rolling of eye balls and involuntary movements of both upper and lower limb. Afterwards she was admitted in ICU. Better vigilance is necessary for implementation of safe and effective treatment for each individual patient. In-order to prevent serious adverse drug reactions of this drug, close monitoring during treatment course, creating awareness, recognition of the problem and careful management of all patients who receive this medication are essential.
Keywords: Selective Serotonin Reuptake Inhibitor; Suspected ADR; Escitalopram; Serotonin syndrome.